Investigating the Possibility of Nurse Prescribing Training Development in Nursing Education System in Iran - Aazam Soltaninejad; Fatemeh Alhani; Maryam Rassouli (Elsevier, 2024)
Summary: Purpose: Adequate medical knowledge and skills are fundamentals for nurse prescribing authority development. This study will explore the potential for developing nurse prescribing training in Iran, where nurses currently lack prescribing authority despite their strong academic nursing education. Methods: This is a study with two phases. At first, in a conventional qualitative content analysis method, with purposive and snowball sampling, from June 2021 to March 2023, 20 participants, including 16 nurses in different clinical, managerial, educational, and policy-making settings, three physicians, and one clinical pharmacist were interviewed. Unstructured interviews were conducted face-to-face or virtually as the situation required during the pandemic period due to Coronavirus disease, 2019 (COVID-19). Qualitative content analysis as developed by Elo and Kyngäs in 2008 was used for data analysis. In the second comparative analysis phase, four masters of science and one doctor of nursing curricula analyzed in the existence of the nurse prescribing prerequisite courses and these five curricula and two potential masters of science in community health and critical care nursing curricula were compared with John Hopkins University curricula. Results: In the qualitative phase, two themes emerged: nursing education challenges and the potential for nurse prescribing training development. These were further broken down into four subthemes: inadequate nurses' knowledge in prerequisite nurse prescribing courses, unprepared educational infrastructure, treatment sector potentials, and educational potentials, with a total of 12 concepts identified. During the comparative phase, it was found that none of the nursing curricula had adequate prerequisite courses for nurse prescribing. However, the Community Health and Critical Care nursing curricula showed potential for developing nurse prescribing training. Conclusions: In the nursing education system, there are some challenges and potentials for prescribing training, and the community health and critical care nursing curricula have the potential capacity to prepare the graduated nurses to prescribe. It needs educational and managerial policies. More developmental research and pilot studies are recommended.